FAKTOR YANG MEMPENGARUHI LAMANYA PELAKSANAAN INISIASI MENYUSU DINI (IMD) PADA IBU POST PARTUM DI BPM ISTIQOMAH, S. Keb.Bd SURABAYA - UKE MAHARANI DEWI (Universitas Nahdlatul Ulama Surabaya, 2017)
Various programs to support the delivery of ASI has intensified coverage of ASI but still does not meet the expected target. The purpose of this study was to determine the relationship between the mother’s attitude, support health workers and support the implementation of those closest to the length of early initiation of breastfeeding on maternal postpartum in BPM Istiqomah, S. Keb.Bd Surabaya. This study is an analityc observational research. Population in this study were all patients post partum in BPM Istiqomah, S. Keb.Bd as many as 15 respondents. Sampling using total sampling. Data collection is done by direct observation by the researcher. Collected data is then processed and analyzed using a computer. Data analysis include univariate analyzes looking for frequency distribution, bivariate analysis with chi square correlation fisher exact test (α<0,05). The results of the bivariate analysis showed a significant relationship (significant) between the attitude of the mother, the support of health professionals, and the support of those closest to the duration of the early initiation of breastfeeding on post partum mothers with significant value smaller than 5%. Key word: attitude, the support of health professionals, and the support of those closest, the duration of the early initiation of breastfeeding> <0,05). The results of the bivariate analysis showed a significant relationship (significant) between the attitude of the mother, the support of health professionals, and the support of those closest to the duration of the early initiation of breastfeeding on post partum mothers with significant value smaller than 5%.